A new species of crane fly, Pedicia (Pedicia) goldsworthyi (Diptera: Pediciidae), from eastern North America - Petersen, Matthew J. (Zootaxa, 2006)
A new species of crane fly, Pedicia (Pedicia) goldsworthyi, is described from eastern North America. The range of this species is extensive, from Maine to North Carolina, and broadly overlaps with the ranges of the four other regional species of Pedicia (Pedicia) Latreille. A key to males of the eastern North America species of Pedicia (Pedicia) that includes this new species is presented.